Self-regulated learning sebagai mediator keterlibatan orang tua dan prestasi akademik siswa SMA - Freddy, Freddy; Lestari, Sri; Prihartanti, Nanik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract Academic achievement is an important indicator of academic success. This study aims to analyze the effect of self-regulated learning in mediating the effect of parental involvement on academic achievement. Data collection for participants in this study (n = 206) was carried out using the convenience sampling technique. The validity of the items in the instrument was tested with the content validity index (CVI) and the reliability test used an internal consistency approach. The results of testing the validity of the parental involvement scale showed that the V Aiken coefficient ranged from 0.604-0.964 and Cronbach's alpha coefficient was 0.816, while the Motivated Strategy for Learning Questionnaire scale obtained the V Aiken coefficient between 0.821-0.928 with a Cronbach alpha coefficient value of 0.765 which met the validity and reliability requirements. Data analysis was performed using Structure Equation Modeling (SEM). Based on the research results that self-regulated learning mediates the effect of parental involvement on high school student academic achievement. The implication of this research is the importance of parental assistance in developing students' skills in planning and managing learning activities, not only on student achievement in academics.Keywords: academic achievement; high school students; parental involvement; self-regulated learning. Abstrak Prestasi akademik menjadi salah satu indikator penting dalam keberhasilan pendidikan. Penelitian ini bertujuan untuk menganalisis peran self-regulated learning dalam memediasi pengaruh keterlibatan orang tua terhadap prestasi akademik siswa. Sebanyak 206 orang siswa SMA berpartisipasi dalam penelitian ini. Pengambilan sampel dilakukan dengan menggunakan teknik convenience sampling. Validitas butir pernyataan dalam instrumen diuji dengan content validity index (CVI) dan uji reliabilitas menggunakan pendekatan konsistensi internal. Hasil pengujian validitas skala keterlibatan orang tua menunjukkan koefisien V Aiken berkisar 0,604-0,964 dan koefisien alfa Cronbach sebesar 0,816, sedangkan skala Motivated Strategy for Learning Questionnaire diperoleh koefisien V Aiken antara 0,821-0,928 dengan nilai koefisien alfa Cronbach sebesar 0,765 yang memenuhi persyaratan validitas dan reliabilitas. Data dianalisis dengan structure equation modelling (SEM). Hasil penelitian menunjukkan bahwa self-regulated learning memediasi pengaruh keterlibatan orang tua terhadap prestasi akademik siswa SMA. Implikasi dari penelitian ini adalah pendampingan orang tua pada siswa difokuskan pada upaya mengembangkan keterampilan siswa dalam merencanakan dan mengelola kegiatan belajar, bukan hanya pada capaian akademik siswanya.Kata kunci: keterlibatan orang tua; prestasi akademik; self-regulated learning; siswa SMA